Wellbeing, Freedom and Social Justice The Capability Approach Re-Examined - Robeyns, Ingrid; Open Textbook Library (Open Textbook Library, 2017)
How do we evaluate ambiguous concepts such as wellbeing, freedom, and social justice? How do we develop policies that offer everyone the best chance to achieve what they want from life? The capability approach, a theoretical framework pioneered by the philosopher and economist Amartya Sen in the 1980s, has become an increasingly influential way to think about these issues. Wellbeing, Freedom and Social Justice: The Capability Approach Re-Examined is both an introduction to the capability approach and a thorough evaluation of the challenges and disputes that have engrossed the scholars who have developed it. Ingrid Robeyns offers her own illuminating and rigorously interdisciplinary interpretation, arguing that by appreciating the distinction between the general capability approach and more specific capability theories or applications we can create a powerful and flexible tool for use in a variety of academic disciplines and fields of policymaking. This book provides an original and comprehensive account that will appeal to scholars of the capability approach, new readers looking for an interdisciplinary introduction, and those interested in theories of justice, human rights, basic needs, and the human development approach.
Acknowledgements -- 1. Introduction -- 1.1 Why the capability approach? -- 1.2 The worries of the sceptics -- 1.3 A yardstick for the evaluation of prosperity and progress -- 1.4 Scope and development of the capability approach -- 1.5 A guide for the reader -- 2. Core Ideas and the Framework -- 2.1 Introduction -- 2.2 A preliminary definition of the capability approach -- 2.3 The capability approach versus capability theories -- 2.4 The many modes of capability analysis -- 2.5 The modular view of the capability approach -- 2.6 The A-module: the non-optional core of all capability theories -- 2.7 The B-modules: non-optional modules with optional content -- 2.8 The C-modules: contingent modules -- 2.9 The modular view of the capability account: a summary -- 2.10 Hybrid theories -- 2.11 The relevance and implications of the modular view -- 2.12 A visualisation of the core conceptual elements -- 2.13 The narrow and broad uses of the capability approach -- 2.14 Conclusion -- 3. Clarifications -- 3.1 Introduction -- 3.2 Refining the notions of 'capability' and 'functioning' -- 3.3 Are capabilities freedoms, and if so, which ones? -- 3.4 Functionings or capabilities? -- 3.5 Human diversity in the capability approach -- 3.6 Collective capabilities -- 3.7 Which notion of wellbeing is used in the capability approach? -- 3.8 Happiness and the capability approach -- 3.9 The capability approach and adaptive preferences -- 3.10 Can the capability approach be an explanatory theory? -- 3.11 A suitable theory for all normative questions? -- 3.12 The role of resources in the capability approach -- 3.13 The capability approach and theories of justice -- 3.14 Capabilities and human rights -- 3.15 Conclusion -- 4. Critiques and Debates -- 4.1 Introduction -- 4.2 Is everything that's called a capability genuinely a capability? -- 4.3 Should we commit to a specific list of capabilities? -- 4.4 Why not use the notion of needs? -- 4.5 Does the capability approach only address the government? -- 4.6 Is the capability approach too individualistic? -- 4.7 What about power and political economy? -- 4.8 Is the capability approach a liberal theory? -- 4.9 Why 'human development' is not the same idea -- 4.10 Can the capability approach change welfare economics? -- 4.11 Taking stock -- 5. Which Future for the Capability Approach? -- References -- Index
In English.
Description based on online resource
Keywords: Social sciences -- Textbooks; Political Science -- Textbooks; Philosophy -- Textbooks; Economics -- Textbooks